Mobile Users and Service Experience Developers - Sarmento, Teresa (2010)
Customer Experiences have become increasingly important as well as challenging to differentiate and add value to products and services. Experiences play a particularly important role in the emerging field of service development and design, as value is cocreated by customers through their interactions with service providers resulting in a unique contextual outcome (Stuart and Tax 2004; Mager 2009). Services are relational and require shared knowledge and background between a company and its costumers (Verhoef, Lemon et al. 2009). Therefore it is considered more difficult to create valuable service experiences when the company is not present (Sandstrom, Magnusson et al. 2009; Verhoef, Lemon et al. 2009), and some authors advocate further research to create memorable service experiences through the design of new interactive applications, its interfaces and its specific mobility (R.S. Subramanya 2007). This research contributes to a better understanding of user’ experience requirements in mobile services and to improve its incorporation into New Service Development. This article reports the results of two qualitative studies that explored experiential factors in mobile services covering regular users of mobile services and designers/developers’perspectives. The first study involved in-depth interviews and focus groups with 25 users of mobile phone services, focusing on the experiential factors of a mobile loyalty service and analyzing existing services. The second study involved a sample of 82 individuals (mainly designers - 52, 6%), during a creative training course on innovation. Mental modelling supported the design of an imaginary mobile service interface through a codiscovery method. Following qualitative methods (Charmaz 2006), both studies were transcribed and analyzed to identify categories of service experience requirements. The analysis accomplishes a comparative assessment of the experiential factors identified by regular users as well as endorsed the identification of requirements influencing mobile service experiences from the designers’ perspective describing it with their own language code. The results of the study with mobile service users allowed for an in-depth understanding of the user experience, which are not strictly related to the design of the interaction device. According to study results, one of the most important factors influencing the mobile service experience is the interaction with service merchants, and the service environment in which the mobile service is used. This subject is relevant when people prefer some mobile systems due to factors such as emotional experiences that might play an important role in addition to functional aspects(Thüring 2007). Other factors such as ease use and its trade-off relationship with privacy, ease of learning, data usage, visualization, were also deemed important. The designers’ group also pointed out some of the experience factors already identified by users, such as ease of use and efficiency, but they paid much more attention to the functional and technological aspects surrounding mobile phones in comparison to the service characteristics. This fact may be a result of their professional backgrounds. This two-way analysis places two unlike approaches and as a result similarities and differences can be identified on how the service processes, and the way interface is used. Although the usability and performance factors are mentioned by both groups, designers do not address the contextual elements that have a strong influence in the overall customer experience, such as the service environment, the service process. This perspective has eased the understanding of the differences and priorities of experience in a mobile loyalty service according to developers and regular user’s perception. Furthermore it has helped to identify the service design elements that affect users and developers’ experiences, such as the interface and the service context of use, and to find their specific responsiveness to the interaction process. This points out to the need of a more collaborative approach from both stances. We believe that this work can contribute to increase this collaboration and therefore add value to service innovation. The New Service Development demands a good understanding of the user’s service experiences, as well as developers that must be aware of this complete service scope.